English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-10-30 12:35:22 · 3 answers · asked by David 1 in Science & Mathematics Mathematics

3 answers

Use the multiplication rule. if you have f(x)g(x)
then the answer is f ' (x)g(x) + f(x)g ' (x)

also, don't forget the chain rule

therefore

f ' (x) = ((2x+1)^.5) + x(.5(2x+1)^-.5)2)
f ' (x) =((2x+1)^.5) + x((2x+1)^-.5))

2007-10-30 12:45:15 · answer #1 · answered by Ryan 4 · 0 0

x √(2x + 1)

product rule:

d/dx (uv) = u'v + v'u

d/dx (x) √(2x + 1) + d/dx √(2x + 1) x

d/dx (x) = 1

√(2x + 1) + d/dx √(2x + 1) x

use the chain rule:
let u = 2x + 1
then d/du (u) = 1/(2√u)
d/dx (2x + 1) = 2

√(2x + 1) + 1/(2√(2x + 1)) * 2 * x

√(2x + 1) + x/√(2x + 1) <== answer

2007-10-30 19:42:41 · answer #2 · answered by Anonymous · 0 0

x/(2x+1)^.5 + (2x+1)^.5

2007-10-30 19:41:51 · answer #3 · answered by ironduke8159 7 · 0 0

fedest.com, questions and answers